1996
DOI: 10.1146/annurev.phyto.34.1.325
|View full text |Cite
|
Sign up to set email alerts
|

Root System Regulation of Whole Plant Growth

Abstract: New evidence confirms earlier postulates that root signals to shoots, including abscisic acid, nitrate flux, and cytokinins, modify whole plant growth processes including leaf expansion, stomatal behavior, and biosynthesis of photosynthetic enzymes. Root signals are thought to reflect soil water, nutrient, and mechanical attributes, as sensed by roots. Meristematic activities in root tips initiate changes in root architecture, modifying the soil volume subject to root uptake, and may provide multiple sensory a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(73 citation statements)
references
References 68 publications
2
69
0
2
Order By: Relevance
“…& E.H. Wilson seedlings were increased by elevated temperature (Ormrod et al 1999;Yin et al 2008). Another study pointed out that roots would synthesize and export more cytokinin to foliage to promote pigment synthesis under more favourable temperatures (Aiken and Smucker 1996). Our results confirm that enhanced photosynthetic pigment content is closely related to the elevated temperature, which suggested our temperature increment might provide near-optimal conditions for pigment biosynthesis.…”
Section: Effects Of Warming and Nitrogen Fertilization On Photosynthesupporting
confidence: 77%
“…& E.H. Wilson seedlings were increased by elevated temperature (Ormrod et al 1999;Yin et al 2008). Another study pointed out that roots would synthesize and export more cytokinin to foliage to promote pigment synthesis under more favourable temperatures (Aiken and Smucker 1996). Our results confirm that enhanced photosynthetic pigment content is closely related to the elevated temperature, which suggested our temperature increment might provide near-optimal conditions for pigment biosynthesis.…”
Section: Effects Of Warming and Nitrogen Fertilization On Photosynthesupporting
confidence: 77%
“…The effects of warming and light regimes on physiological performance Aiken and Smucker (1996) suggested that roots would synthesize and export more cytokinin to foliage to promote pigment synthesis under more favorable temperature conditions. In this study, an increase in Chl a, Chl b, Chl (a + b), and carotenoid concentration for the two conifers in response to warming was observed (Fig.…”
Section: Photosynthetic Parameters Treatmentmentioning
confidence: 99%
“…Addition of inorganic nutrients to the root growing medium of plants subjected to drought stress causes protection of different cellular organelles (Aiken, 1996). Silicon is among the known inorganic nutrients that really may play a role in some physiological processes in plants subjected to drought stress (Habibi and Hajiboland, 2013).…”
Section: Introductionmentioning
confidence: 99%